In Vitro Evaluation of Mechanical Properties of Cention N and Its Comparison with Resin Modified Glass Ionomer Cement (RMGIC) Restorative Material as Used in Primary Teeth - Deepika Pai; P. A. Anirudhmaadhava; Kishore Ginjupalli (The Scientific World Journal)
Background and Objectives. The child’s behaviour and cooperating ability are a crucial factor in deciding the restorative material for pediatric patients. Among the adhesive materials, glass ionomer cement has been the choice of restorative material while restoring primary teeth. However, due to poor physical properties such as wear resistance and water sorption, resin modified glass ionomer cements and composites that are light-cured adhesive restorative materials are preferred. Since the introduction of Cention N, as a self-cured smart alkasite material for restoration, some studies have demonstrated superior mechanical properties in comparison with conventional glass ionomers, modified glass ionomers, and composites. Predominantly, these studies evaluated properties such as microleakage, fluoride release, and marginal adaptation. We conducted this study to evaluate the compressive strength, flexural strength, and shear bond strength of Cention N in the primary teeth. Methods. 22 specimens prepared with Cention and RMGIC were embedded in primary teeth mounted in acrylic for analysing shear bond strength. Shear bond strength was analysed using a universal testing machine. The modes of failure in samples were observed under a stereomicroscope and scanning electron microscope. 22 customised samples of Cention N and RMGIC were prepared and categorised as group A and group B, respectively. The flexural and compressive strengths of these samples were evaluated using a universal testing machine. Results. The shear bond strength of RMGIC was higher than that of Cention N, whereas the compressive and flexural strengths of Cention N were significantly higher than those of RMGIC. The modes of failure were predominantly adhesive followed by mixed failures. Conclusion. The results of this study suggest that Cention N demonstrated superior mechanical properties compared with RMGIC and can therefore be recommended for restorations in primary posterior teeth. Cention N being a smart, esthetic, self-cured, or dual-cured material with better mechanical properties offers a wide range of applicability in primary teeth.